2019
DOI: 10.1503/cjs.018318
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind randomized controlled trial of total knee replacement using patient-specific cutting block instrumentation versus standard instrumentation

Abstract: Background: Patient-specific cutting blocks in total knee arthroplasty have been promoted to improve mechanical alignment, reduce alignment outliers and improve patient outcomes. The aim of this study was to compare the efficacy of patientspecific instrumentation (PSI) and conventional instrumentation (CI) in achieving neutral alignment and accurate component positioning in total knee arthroplasty. Methods: We conducted a double-blinded randomized controlled trial in which patients were randomly assigned to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Other authors have reported, up to 8,5% of cuts being suboptimal using conventional techniques [ 22 ]. Several other studies have demonstrated that factors such as the optimal surgical techniques [ 22 , 23 ], the use of computer navigation [ 24 ], or patient-specific instruments [ 25 , 26 ] are able to improve the outcome of patients. Especially the use of computer navigation and the use of PSI are thought to overcome the above mentioned accuracy limitations at the cost of the investment and more surgical time in case of computer navigation.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have reported, up to 8,5% of cuts being suboptimal using conventional techniques [ 22 ]. Several other studies have demonstrated that factors such as the optimal surgical techniques [ 22 , 23 ], the use of computer navigation [ 24 ], or patient-specific instruments [ 25 , 26 ] are able to improve the outcome of patients. Especially the use of computer navigation and the use of PSI are thought to overcome the above mentioned accuracy limitations at the cost of the investment and more surgical time in case of computer navigation.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32]34 Since it is an inhibitor of TPA, and since both TXA and PAI-1 are important inhibitors of fibrinolysis, their synergism can result in a greater antifibrinolytic effect. 30 The main surgical difference between CI and PSI is that the former implies marrow perforation, 3,5,8,10 which alone could possibly explain the superior results of CI when combined with the use of TXA in terms of blood loss. Not only the highly invasive surgery has been shown to promote a hypercoagulable state, 21 which results in lower blood loss, but also there is PAI-1 production at the site of tissue injury resulting from inflammation associated with the surgical incision.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Conventional instrumentation (CI), the standard option for TKA, uses intramedullary and/or extramedullary alignment systems that rely too much on visual references which can lead even an experienced surgeon to produce undesired postoperative axes. 5,8,10 These devices not only complicate the workflow and prolong surgery time but also can increase blood loss and the risk of fat embolism, as they are more invasive. 5,10 Patient-specific instrumentation (PSI) emerged in the last two decades as an alternative to CI, aiming to improve accuracy and cost effectiveness in daily use, as well as reduce operating times, and blood loss caused by TKA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 During the past decade, patientspecific instrumentation (PSI) has been commercially introduced to simplify and make TKA surgery more precise, effective, and efficient. Several studies, systematic reviews, and meta-analysis [2][3][4][5][6][7][8][9][10][11][12][13][14][15] have been published examining the efficacy of PSI in accurately reproducing a neutral mechanical axis in coronal alignment. Most contemporary publications do not claim a significant increase in PSI accuracy over conventional mechanical instrumentation (CI), but they also do not postulate PSIs accuracy is worse.…”
mentioning
confidence: 99%